Tight-binding study of nonmagnetic-defect-induced magnetism in graphene: Graphene and graphite multilayers - Kumazaki, H.; Hirashima, D.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
This review describes a study of nonmagnetic-defect-induced magnetism of graphene on the basis of a tight-binding model. A vacancy induces a quasilocalized impurity state at the chemical potential around itself, and it leads to formation of local magnetic moments. Connection between a quasilocalized state around a vacancy and the edge localized states near a zigzag edge is studied in detail. Magnetism associated with many vacancies and edge structures is also reviewed. Some new results of magnetism associated with many vacancies are presented.